# Find the roots of the quadratic equation 6x^{2} - x - 2 = 0

**Solution:**

Let us find the roots of the quadratic equation by splitting the middle term.

⇒ 6x^{2} - x - 2 = 0

Split bx into such a way that it is equal to a×c

- 1x can be split into - 4 and 3. [ ∵ (- 4) × (3) = 12].

⇒ 6x^{2} - x - 2 = 0 can be written as

⇒ 6x^{2} + 3x - 4x - 2 = 0

Taking out the common factors

⇒ 3x (2x + 1) - 2(2x + 1)

⇒ (2x + 1)(3x - 2)

Put the both the factors equal to 0

⇒ 2x + 1 = 0 and 3x - 2 = 0.

⇒ x = -1/2 and x = 2/3 are the solutions of the equation

The roots of the equation 6x^{2} - x - 2 = 0 are 2/3 and - 1/2 which satisfies the equation

☛ Check: NCERT Solutions for Class 10 Maths Chapter 4

## Find the roots of the quadratic equation 6x^{2} - x - 2 = 0

**Summary:**

The roots of the equation 6x^{2} - x - 2 = 0 are 2/3 and -1/2 which satisfies the equation

**☛ Related Questions:**

- Check whether the following are quadratic equations: (i) (x - 2)
^{2}+ 1 = 2x - 3 (ii) x (x + 1) + 8 = (x + 2) (x - 2) (iii) x (2x + 3) = x^{2}+ 1 (iv) (x + 2)^{3}= x^{3}- 4 - Find the roots of the equation 2x
^{2}- 5x + 3 = 0, by factorisation - Represent the following situations mathematically: (i) John and Jivanti together have 45 marbles. Both of them lost 5 marbles each, and the product of the number of marbles they now have is 124. We would like to find out how many marbles they had to start with...

Math worksheets and

visual curriculum

visual curriculum